IMPLEMENTASI PROGRAM ONE VILLAGE ONE PRODUCT (OVOP) DALAM MEMBANGUN EKONOMI LOKAL DI KECAMATAN SILUNGKANG KOTA SAWAHLUNTO - Annisa Fitri (Program Magister Ilmu Hukum Universitas Ekasakti, 2022)
The One Village One Product (OVOP) program has been recognized as an effective approach to building the local economy and improving the welfare of people in various regions. In Silungkang, Sawahlunto City, OVOP emerged as a promising strategy to explore the local potential and develop superior products based on local culture and expertise. This research aims to analyze the implementation of OVOP in Silungkang and evaluate its impact on local economic development. The research method used is qualitative by conducting case studies in Silungkang. Data were analyzed descriptively and the research results were presented in narrative form. The research results show that the implementation of OVOP in Silungkang has a positive impact on building the local economy and improving people's welfare. The economic impacts arising from the implementation of OVOP in Silungkang include increasing people's income, creating jobs, and increasing the competitiveness of local products. However, there are several challenges in implementing OVOP in Silungkang, such as limited access to broader markets, coordination between institutions that need to be strengthened, and the need to increase supporting infrastructure. Therefore, it is suggested to increase investment in the promotion and marketing of local products, strengthen cooperation among stakeholders and invest in infrastructure that supports local economic development.